A prospective, multicentre, randomised controlled study of human fibroblast‐derived dermal substitute (Dermagraft) in patients with venous leg ulcers. Issue 2 (19th March 2013) - Harding, Keith; Sumner, Michael; Cardinal, Matthew
Abstract This was an open‐label, prospective, multicentre, randomised controlled study to evaluate the efficacy and safety of human fibroblast‐derived dermal substitute (HFDS) plus four‐layer compression therapy compared with compression therapy alone in the treatment of venous leg ulcers. The primary outcome variable was the proportion of patients with completely healed study ulcers by 12 weeks. The number healed was further summarised by ulcer duration and baseline ulcer size. Sixty‐four (34%) of 186 patients in the HFDS group experienced healing by week 12 compared with 56 (31%) of 180 patients in the control group (P = 0·235). For ulcers ≤ 12 months duration, 49 (52%) of 94 patients in the HFDS group versus 36 (37%) of 97 patients in the control group healed at 12 weeks (P = 0·029). For ulcers ≤ 10 cm2, complete healing at week 12 was observed in 55 (47%) of 117 patients in the HFDS group compared with 47 (39%) of 120 patients in the control group (P = 0·223). The most common adverse events (AEs) were wound infection, cellulitis and skin ulcer. The frequency of AEs did not markedly differ between the treatment and control groups.